KEMAMPUAN MENULIS PERMULAAN PESERTA DIDIK KELAS 1 PADA MATA PELAJARAN BAHASA INDONESIA DI SDN 1 TRENCENG SUMBERGEMPOL TULUNGAGUNG - Yudha Prawira Kusuma; Frita Devi Asriyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Writing ability is part of the development of interpreted language, namely translating images or symbols into writing that can be combined with words, which are arranged so that people can understand them. The Indonesian language subject is one of the main subjects taught to students from grade I to grade VI in elementary school. Various abilities in Indonesian language lessons to hone language skills consist of listening, speaking, reading and writing skills. This study aims to describe and analyze the initial writing skills of grade 1 students in the Indonesian language subject at SDN 1 Trenceng. The research is based on a descriptive qualitative method. The tools used include observation forms, discussion sheets with three first-year students and teachers, and various documents. The results of the study on the initial writing skills of grade 1 students in the Indonesian language subject at SDN 1 Trenceng. Students (APA, DBA, ZMBS) they have failed to achieve the initial eleven criteria for writing proficiency, as they often spend time playing with friends during learning sessions, tease their peers, have problems remembering which letters to form, their handwriting is untidy, they frequently abbreviate words and usually add to them, have difficulty distinguishing between upper and lower case.The suggestions given based on the results of this study for this study for further researchers are expected that this study can be a reference for initial writing skills in Indonesian language learning subjects and this study can be developed further to be more perfect in the.